THE MODEL OF OPTIMIZING THE SYSTEM OF COMPETITION SUSTAINABILITY MANAGEMENT IN MUNICIPAL FACILITIES - Stepan P. Burlankov (Вестник Российского экономического университета имени Г. В. Плеханова)
The current trends of economy development demonstrate the necessity of taking into account factors of internal and external environment in changing conditions, which can ensure competition sustainability of the enterprise. The author puts forward a model of optimizing the system of competition sustainability management in municipal facilities, where two aspects of this notion can be distinguished: competition sustainability of the enterprise itself, which is characterized by its market potential in the process of work and competitiveness of the service. The model consists of two elements: the first one includes specific cost of planned modernization and capital and routine repairs and the second one – specific costs in operation (costs of emergency and routine repairs, current maintenance of buildings, sanitary keeping of apartment houses and surrounding territory and house-management, cost of idle time). This model differs from the effective one by the fact that instead of resource for municipal facilities’ enterprise the author uses the value of building physical wear.